Social Presence of Ruangguru in Social Media during Covid-19 Pandemic - Fattah, Raihan Abiyan; Sujono, Firman Kurniawan (Universitas Semarang, 2020)
Covid-19 Pandemic gives many social changes in society specially in communications study. One important policy made during Covid-19 is related to students who are required to study at home. Ruangguru is top of mind in digital based learning company, especially during this pandemic. Covid-19 and this policy made Ruangguru as Indonesia online learning company with the most followers, to adapt in giving online communication message, especially in @ruangguru (Instagram). This research aims to see the social presence of Ruangguru in social media (Instagram) during Covid-19 Pandemic through three dimensions of social presence, which are: social context, online communication, and interactivity. On previous research, it was mentioned that social presence relates to brand engagement. Brand's social presence in social media is important to be researched due to more brand using social media as primary communication tool to gain brand engagement. Method used in this research is case study with qualitative approach. Through Ruangguru's post on Instagram, researcher observes using three dimensions of social presence. The result of this research depicts Ruangguru as showing good social presence based on three dimensions of social presence during Covid-19 Pandemic in social media Instagram.